BIOREMEDIASI TANAH YANG TERCEMAR LIMBAH PENGILANGAN MINYAK BUMI SECARA IN VITRO PADA KONSENTRASI pH BERBEDA - Syukria Ikhsan Zam (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2011)
The purposes of this research were to get the best pH, and also to identify the ability of mixed culture of hydrocarbonoclastic bacteria in bioremediation of dirtied soil by oil refinery waste. The bacteria were used are Acinetobacter baumanni, Alcaligenes eutrophus, Bacillus sp1., Methylococcus capsulatus, Bacillus sp2., Morococcus sp., Pseudomonas diminuta, Xanthomonas albilineans, Bacillus cereus and Flavobacterium branchiophiia. Variation of pH were 6,5, 7,0, 7,5. Observed parameters in optimization were Total Plate Count (TPC) the culture every week, Total Petroleum Hydrocarbon (TPH) and Chemical Oxygen Demand (COD) examined at the end of the bioremediation period. Best optimization result then analyzed with GC/MS. The best pH was 7,5 with TPH degradation 73,241% and COD slope 86,283%. The chromatogram indicated that hydrocarbon compound from nC9 – nC32 have been degraded by 31,824% – 94,934%. The conclusions of this research were a good result of bioremediation was obtained from mixed culture inoculum at pH 7,5.